Breaking hackneyed ideas. Women in vocational training - Rubio Herráez, María Esther (Avances en Supervisión Educativa, 2007)
From an up-to-date point of view, the present article deals with the historical change of technological assessment to explain the role that prejudice and vested interests play in the exclusion of women from vocational training. It analyses the historical facts that have occurred from the first craft workshops to the present day.  The 21st century proves as an educational fact that vocational training still bears a mark of segregation and hierarchical structure. Consequently, a debate is still necessary for the improvement of both general education systems and the ones that are specific for vocational training.